Cantharidin as an Alternative Treatment for Genital Warts: A Case Monitored With Optical Coherence Tomography - Ruini, C; Clanner-Engelshofen, B; Heppt, M; Herzinger, T; Sárdy, M; Ruzicka, T; French, L; Reinholz, M (Acta dermato-venereologica, 2020)
Abstract is missing (Short communication)